Acrolein plays a culprit role in the pathogenesis of diabetic nephropathy in vitro and in vivo. Issue 4 (22nd September 2022) - Tong, Zhen-Jie; Kuo, Chin-Wei; Yen, Po-Cheng; Lin, Chih-Ching; Tsai, Ming-Tsun; Lu, Shing-Hwa; Chang, Yi-Ping; Liu, Wen-Sheng; Tsou, Han-Hsing; Cheng, Hsiao-Wei; Wang, Hsiang-Tsui
Abstract: Objective: Diabetic nephropathy (DN), also known as diabetic kidney disease (DKD), is a major chronic complication of diabetes and is the most frequent cause of kidney failure globally. A better understanding of the pathophysiology of DN would lead to the development of novel therapeutic options. Acrolein, an α, β-unsaturated aldehyde, is a common dietary and environmental pollutant. Design: The role of acrolein and the potential protective action of acrolein scavengers in DN were investigated using high-fat diet/ streptozotocin-induced DN mice and in vitro DN cellular models. Methods: Acrolein-protein conjugates (Acr-PCs) in kidney tissues were examined using immunohistochemistry. Renin–angiotensin system (RAS) and downstream signaling pathways were analyzed using quantitative RT-PCR and Western blot analyses. Acr-PCs in DN patients were analyzed using an established Acr-PC ELISA system. Results: We found an increase in Acr-PCs in kidney cells using in vivo and in vitro DN models. Hyperglycemia activated the RAS and downstream MAPK pathways, increasing inflammatory cytokines and cellular apoptosis in two human kidney cell lines (HK2 and HEK293). A similar effect was induced by acrolein. Furthermore, acrolein scavengers such as N-acetylcysteine, hydralazine, and carnosine could ameliorate diabetes-induced kidney injury. Clinically, we also found increased Acr-PCs in serum samples or kidney tissues of DKD patients compared to normal volunteers, and the Acr-PCs were negatively correlated with kidney function. Conclusions: These results together suggest that acrolein plays a role in the pathogenesis of DN and could be a diagnostic marker and effective therapeutic target to ameliorate the development of DN.